COPYRIGHT AND ISLAMIC CONTENT IN THE MEDIA INDUSTRY (MEDIOVA: Journal of Islamic Media Studies, 2025)
The rapid advancement of digital technology has created significant opportunities for the dissemination of Islamic content through social media. However, this development also comes with an increasing prevalence of copyright violations against da'wah content, largely due to weak regulations and insufficient oversight. This study aims to analyze copyright regulations in the media industry, particularly concerning Islamic content, and to identify the challenges faced by creators in producing and distributing their work. Using a library research method, the study finds that current copyright laws still have gaps in protecting Islamic content, both in terms of unauthorized use and restrictions imposed by social media algorithms. Other challenges faced by creators include the risk of false copyright claims, competition with more popular content, and dilemmas related to monetizing da'wah content. Therefore, this study proposes alternative copyright protection mechanisms such as the implementation of open licenses (Creative Commons), blockchain technology, digital watermarking, and the categorization of Islamic content on digital platforms. Collaboration between the government, media platforms, content creators, and Islamic organizations is a key factor in ensuring copyright regulations are enforced effectively without hindering digital da'wah. With more adaptive protection mechanisms, Islamic content can continue to grow as a high-quality medium for education and da'wah while respecting the intellectual property rights of its creators.